A multi‐center, randomized, open‐label, parallel group study of a natural micronized progesterone vaginal tablet as a luteal support agent in Japanese women undergoing assisted reproductive technology. (14th June 2015) - Fujiwara, Toshihiro
Abstract: Purpose: To verify sufficient progesterone supplementation during the luteal phase and to determine the efficacy and safety of a natural micronized progesterone vaginal tablet (FE 999913) in Japanese women undergoing in vitro fertilization‐embryo transfer or intracytoplasmic sperm injection. Methods: In a multi‐center, randomized, open‐label, parallel group trial, 108 subjects were randomized to receive FE 999913 vaginally twice daily ( n = 54) or three times daily ( n = 54) for up to 10 weeks. Primary endpoints were the proportion of subjects with serum progesterone concentration ≥10 ng/ml on day 5 and ongoing pregnancy rate at week 5. Results: Ninety‐four subjects completed the trial and 90 subjects underwent embryo transfer. The proportion of subjects with serum progesterone concentration ≥10 ng/ml on day 5 was 98.9 % and the lower limit of 95 % CI of the difference between the current trial and MEGASET trial was −3.6 %, which was within the non‐inferiority criterion. The ongoing pregnancy rate was 22.2 %, which is similar to that in actual clinical settings in Japan. No safety concerns were observed. Conclusions: FE 999913 was useful in this trial from the aspects of sufficient supplementation of progesterone, comparable pregnancy rate with that in clinical practice in Japan, and safety. Clinical trial registration: ClinicalTrials.gov identifier: NCT01710514.